1999
DOI: 10.1149/1.1392657
|View full text |Cite
|
Sign up to set email alerts
|

Probing Coating Degradation on AA2024‐T3 Using Local Electrochemical and Chemical Techniques

Abstract: The service life of an organic coating on a metal substrate is determined by variables associated with the environment, the coating, the substrate, and the interphasial chemistry that develops between the substrate and the coating. Although our basic understanding of the corrosion and materials issues within each of these regions is increasing, our understanding of the interactions among them and how these interactions lead to failure is limited. This gap in understanding is, in part, associated with the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 24 publications
0
33
0
2
Order By: Relevance
“…An analysis of the distribution of intermediate diffuse layers showed that their growth followed a parabolic law previously described by Frenkel and Sergeev. The degradation of coatings on the AA2024-T3 alloy was studied in [47], and the composition of the wearing products of multilayer metal coatings was determined in [48]. Electrochemical criteria for assessing the quality of protective coatings were considered in [49], such as the surface distribution of the thickness and composition of coatings, the protective capacity and porosity of coatings, and the integral characteristic of the quality of coatings.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…An analysis of the distribution of intermediate diffuse layers showed that their growth followed a parabolic law previously described by Frenkel and Sergeev. The degradation of coatings on the AA2024-T3 alloy was studied in [47], and the composition of the wearing products of multilayer metal coatings was determined in [48]. Electrochemical criteria for assessing the quality of protective coatings were considered in [49], such as the surface distribution of the thickness and composition of coatings, the protective capacity and porosity of coatings, and the integral characteristic of the quality of coatings.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…[12,13] In order to evaluate the critical factors that trigger initiation and propagation of localized corrosion local techniques are frequently applied to gain a better insight in the mechanisms of pitting. Several groups used in situ scanning techniques to track the evolution of the surface topography during pitting, [14,15] local pH values, [16,17] local impedance, [16] and local current densities. [18] The sulfate and chloride accumulation in the passive film during and after the breakdown of the passive film was also studied with radiotracer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen clearly that the aliphatic carbon is found in high concentrations in the region surrounding the pit. The hydrocarbons could be due to acetone (CH 3 COCH 3 ), acetic acid (CH 3 COOH) or acetate (CH 3 COO ) as in copper acetate (Cu(CH 3 COO) 2 ) and aluminum acetate (Al(CH 3 COO) 3 ). They could be due also to the sum of all these components.…”
Section: Resultsmentioning
confidence: 99%